PEMETAAN KEMISKINAN KABUPATEN/KOTA DI PROVINSI JAWA TENGAH TAHUN 2002 DAN 2010 MENGGUNAKAN ANALISIS KLASTER - Minawati Widiastuti; Edy Yusuf A. G. (Diponegoro Journal of Economics, 2012)
ABSTRACT Poverty is the problems from year to year included in the list of national strategic research. Many efforts have been conducted to poverty alleviation. Poverty alleviation who has done by government tending to make poor people become increasingly depending on the aid by foreign parties and not right on the target. To support the success of the program poverty alleviation in the Province of Central Java required a research that can classify distric that had the characteristic of poverty that nearly equal to or homogeny. This research grouping district in the Province of Central Java to 6 clusters based on a indicator poverty by using analysis cluster. The variable that is used to classify district in Central Java are 15 variables which is an indicator of poverty. The result showed that the division of a cluster 6, the region of the poorest are in a cluster 4 and in each cluster can be known which variables are the most dominant influence poverty a distric in Central Java. Then when compared between 2002 and 2010 can be known that occur distinction members of each cluster because a district changes during the period of 8 years.